Museum Digitisations and Emerging Curatorial Agencies Online - Axelsson, Bodil. author. aut Link
XV, 138 p. 13 illus., 12 illus. in color.
Keywords: This open access book explores the multiple forms of curatorial agencies that develop when museum collection digitisations, narratives and new research findings circulate online. Focusing on Viking Age objects, it tracks the effects of antagonistic debates on discussion forums and the consequences of search engines, personalisation, and machine learning on American-based online platforms. Furthermore, it considers eco-systemic processes comprising computation, rare-earth minerals, electrical currents and data centres and cables as novel forms of curatorial actions. Thus, it explores curatorial agency as social constructivist, semiotic, algorithmic, and material. This book is of interest to scholars and students in the fields of museum studies, cultural heritage and media studies. It also appeals to museum practitioners concerned with curatorial innovation at the intersection of humanist interpretations and new materialist and more-than-human frameworks. Bodil Axelsson is Professor of Cultural Heritage at Linköping University, Sweden. She researches across the fields of critical heritage studies, digital media and museology, and has led and coordinated a series of research projects within these fields. Fiona R Cameron is Associate Professor, Contemporary Museologies at the Institute for Culture and Society, Western Sydney University, Australia. Cameron is a pioneering figure in digital heritage studies, museum theory and museum engagement with controversial topics and climate action. Fiona has published 83 books and articles with leading publishers on these topics. Katherine Hauptman is Director at the Swedish History Museum and holds a Ph.D. in Archeology. She has a wide portfolio of experience in museum studies, education, governmental assignments and exhibition production. Hauptman has published books on Nordic and public archeology, heritage studies including gender perspectives, the uses of history and inclusive museums. Sheenagh Pietrobruno is Associate Professor of Social Communication at Saint Paul University/University of Ottawa, Canada. She has held fellowships in England, Canada, Sweden and Austria in media, performance, and heritage research. European Commission (2019) and G20 Italian Presidency (2021) invitations to present her pioneering work in digital (intangible) heritage have impacted policy.